Brief Report: Enhanced Allogeneic Cellular Responses to Mismatched HLA-B Antigens Results in More Efficient Killing of HIV Infected Cells. (15th April 2016) - Sabbaj, Steffanie; Scanlon, Nicholas; Du, Victor Y.; Wang, Yuge; Tang, Jianming; Hunter, Eric; Goepfert, Paul A.
Abstract : Abstract: Epidemiologic studies have demonstrated that HIV-1 discordant couples who share HLA-B alleles were more likely to transmit HIV-1. These data lead us to hypothesize that individuals who match at both HLA-B alleles should have a reduced allogeneic response than those who are not matched. We observed diminished killing of CD4 + target cells only when HLA-B alleles were matched. We propose that for cell-associated HIV-1 transmission, the ability of the recipient to eliminate infected cells from a donor partner may be enhanced when HLA-B alleles are different between partners. These findings suggest a novel mechanism for protection against HIV infection.